Psychomotor activity and body weight gain after exposure to low ribavirin doses in rats: Role of treatment duration - Petković, Branka; Stojadinović, Gordana; Kesić, Srđan; Ristić, Slavica; Martać, Ljiljana; Podgorac, Jelena; Pešić, Vesna (Archives of Biological Sciences, 2019)
Paper description: Ribavirin is an antiviral agent showing side effects associated with use of high doses and/or long-term application. This study examined the effects of single or repeated application of low ribavirin doses (10, 20 and 30 mg/kg/day, i.p.) on dopamine-mediated behaviors, novelty-induced investigation and d-amphetamine-induced motor activity, and on body weight gain in adult male rats. Hypolocomotion and reduced weight gain in a U-shaped dose-response related manner were observed after repeated ribavirin treatment. The findings contribute to an improved understanding of the psychomotor and physiological responses to low ribavirin doses in the rodent model with regard to treatment duration. Abstract: Clinically-related basic studies on the behavioral effects of ribavirin treatment are still lacking despite its wide use as an antiviral medication. This paper considers the effects of low ribavirin doses (10, 20 and 30 mg/kg/day) on psychomotor activity (novelty-induced exploratory behavior, d-amphetamine (AMPH, 1.5 mg/kg, intraperitoneal)-induced motor activity), and body weight gain in socially undisturbed adult male Wistar rats 24 h after the first, seventh and fourteenth once-a-day injection. Low doses of ribavirin were tested in an attempt to avoid the recognized systemic side effects related to high-dose usage. None of the singly applied ribavirin doses affected exploratory/spontaneous and AMPH-induced motor behavior (locomotion, stereotypy-like and vertical activity), however, body weight gain was significantly lower after treatment with 30 mg/kg of ribavirin. The 7- and 14-day treatments with 10 and 30 mg/kg/day of ribavirin significantly suppressed novelty-induced locomotion and body weight gain; the 14-day treatment with ribavirin at a dose of 30 mg/kg/day decreased AMPH-induced stereotypy. These findings indicate that repeated application (up to 14 days) of low ribavirin doses results in low novelty-induced locomotion along with reduced weight gain, accentuating the existence of a U-shaped dose-response relationship with a prolonged duration of ribavirin treatment. https://doi.org/10.2298/ABS190205018P Received: February 5, 2019; Revised: March 13, 2019; Accepted: March 22, 2019; Published online: March 25, 2019 How to cite this article: Petković B, Stojadinović G, Kesić S, Ristić S, Martać Lj, Podgorac J, Pešić V. Psychomotor activity and body weight gain after exposure to low ribavirin doses in rats: role of treatment duration Arch Biol Sci. 2019;71(2):357-68.